The affair eaudiobook Anetakis tycoons series, book 3. - Banks, Maya (The Anetakis Tycoons, 2016)
It was only supposed to be a vacation romance. Passionate, exciting-and short-lived. But when Jewel Henley arrived for her first day of work at a new job, she realized her exotic lover was in fact Piers Anetakis, her boss. A boss who had a strict rule about not getting involved with his employees. And so, just like that, Jewel was fired. With no money and no job, Jewel doubted it could get any worse. Then she discovered she was pregnant, and that she'd have to confront Piers. Piers stormed back into her life with the same passion and intensity that had swept her off her feet five months before. But as loving as he was with her, she knew he still didn't trust her. And until he did, all they had.was an affair. BONUS BOOK INCLUDED IN THIS VOLUME! One Night.Nine-Month Scandal by USA TODAY bestselling author Sarah Morgan For English schoolteacher Kelly Jenkins, a Ferrari in her sleepy village can only mean one thing-her ex Alekos Zagorakis has come back to claim what's his.including Kelly.